Preparation and characterization of flexible ferromagnetic nanocomposites for microwave applications - Thomas, Teena; Kanoth, Bipinbal P.; Nijas, C. M.; Joy, Pattayil Alias; Joseph, Joseph M.; Kuthirummal, Narayanan; Thachil, Eby T. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2015)
Magnetic Fe3O4 nanoparticles (similar to 20 nm) were synthesized using the chemical co-precipitation method with a view of developing flexible and easily processable ferromagnetic materials with high mouldability to be used as microwave absorbers. The nanoparticles prepared were incorporated into natural rubber through latex stage processing. This novel processing method gives better dispersion of particles in the rubber matrix. The composites were characterized using XRD, SEM, vibrating sample magnetometer, dynamic mechanical analyzer, cavity perturbation, thermogravimetry (TGA), and Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). A notable improvement in the mechanical properties of composites was observed upon adding Fe3O4 particles. Magnetic and microwave characteristics of the composites indicate the formation of a flexible ferromagnetic material with good microwave absorption characteristics. (C) 2015 Published by Elsevier B.V.
Keywords: Fe3O4; Ferromagnetic; FTIR-PAS; Microwave absorption; Natural rubber; SEM; XRD